(untitled) (Perner’s Contacts, 2009)
Containerization made a revolution in sea transport. It accelerated transport of cargo from consignor to consignee in the logistics chain. Container ships which are important part of container transport have passed through considerable changes. They import more than 90 percent of cargo to Europe.